A Qualitative Exploratory Study of the Effects of Simulation on Nursing Students' Self-Efficacy Beliefs for Using English for Professional Purposes. (February 2022) - Karaçay, Pelin; Zeybekoğlu, Zuhal; Chizzo, Jacob; Middlebrooks, Amy K.
Background: The health sector has become more international than ever because of patients' increased mobility and access to healthcare services. As a result, the ability to communicate in English has become critical for nursing students in countries where English is used as a foreign language. Aim: This study aimed to highlight and understand the experiences of nursing students regarding the effect of simulation-based learning on their self-efficacy beliefs for using English for professional purposes. Methods: The study was conducted with 28 third-year university nursing students enrolled in a required English course and participating in two nursing simulations conducted in English. Focus groups were conducted using semi-structured interview questions to elicit and understand the self-efficacy beliefs of nursing students for using English for professional purposes. The collected data were analyzed by using content analysis. Results: The result of the study emerged under three themes: carrying out nursing duties by using professional discourse, building professional relationships with patients, and maintaining spontaneous conversations with patients. The overall results showed that while the students' self-efficacy beliefs increased for performing standard nursing duties and establishing rapport with patients, no increase was observed in their self-efficacy beliefs for holding a prolonged conversation with the patient. Conclusion: This study's findings have implications for nursing programs in which English proficiency is considered an important program outcome for nurses who may be expected to work in both their own language and English.